KOMPOSISI KIMIA DAGING SEGAR DAN SIFAT ORGANOLEPTIK KELELAWAR OLAHAN - Ransaleleh, Tiltje Andretha (ZOOTEC, 2016)
CHEMICAL COMPOSITION AND ORGANOLEPTIC CHARACTERISTICS OF PROCESSING BAT (Pteropus alecto) FRESH MEAT. Study was done to evaluate chemical composition and preference degree of the consumers on the processing bat meat compared with beef, chicken and cakalang fish using steam cooking method, flavor cooking and spicy cooking method. Chemical composition was analyzed by proximate analysis using procedures of the Association of Official Analytical Chemists. The organoleptic test was done by hedonic test. Data of the hedonic test were analyzed using Kruskal-Wallis method. To evaluate data distribution of the panelist respons on the sample test, the data were using plot graphic box. The hedonic scales were using 1 to 7. The variables used were includingÂ color, taste, flavor, tenderness and general acceptance. Results of proximate analyses of bat meat based on fresh meat indicated that water content was 67.21 percents and protein was 20.48 percents. Based on dry matter, the protein contents of bat meat, pork, chicken, and cakalang fish were 48.97 percents, 69.08 percents, 67.14 percents, and 69.41 percents, respectively. The water contents were 5.76 percents, 9.92 percents, 8.27 percents, and 9.90 percents, repsectively; the calcium (Ca) contents were also 10.62 percents, 1.09 percents, 1.36 percents, 1.38 percents, respectively; while Phosphor (P) contents were 1.46 percents, 0.69 percents, 0.66 percents, and 0.72 percents, respectively. Variance analysis for organoleptic test showed that meat type with different processing affected significantly on taste, color, flavor, tenderness and general preference of bat meat, beef meat, chicken meat and cakalang fish by steam cooking, chicken flavor, and spicy cooking methods. Conclusion, bat meat contained protein relatively lower than that in pork meat, chicken meat, and cakalang fish, but mineral contents were relative higher. Results of organoleptic test showed that preference degree of processing meat were higher on using spicy flavor. The specific test on taste, color, flavor, tenderness and general responsed showed relatively the same responses by the panelists. Â  Key word: Chemical composition, organoleptic test, processing bat meat